Prognostic impact of biologically equivalent dose in stereotactic body radiotherapy for renal cancer. (March 2023) - Tran, Kevin T.; Chevli, Neil C.; Messer, Jay A.; Haque, Waqar; Farach, Andrew M.; Satkunasivam, Raj; Zhang, Jun; Darcourt, Jorge; Lo, Simon S.; Siva, Shankar; Butler, Edward B.; Teh, Bin S.
Highlights: Increasing BED in SBRT is associated with improved overall survival in renal cancer patients. Increasing dose should be encouraged when safe. Prospective investigation needed to validate. Abstract: Purpose /Objectives Materials/Methods: The National Cancer Database (NCDB) was queried (2004–2017) for patients with RCC who did not have surgical resection but received definitive SBRT. Kaplan-Meier analysis with log-rank test was used to evaluate overall survival (OS). Univariable (UVA) and multivariable (MVA) analysis were conducted using cox proportional hazard models to determine prognostic factors for OS. Results: A total of 344 patients with median age 77 (IQR 70–85) were included in this study. Median BED3 was 180 Gy (IQR 126.03–233.97). Median OS was 90 months in the highest quartile compared to 36–52 months in the lower three quartiles (p < 0.01). On UVA, the highest BED3 quartile was a positive prognostic factor (HR 0.67, p < 0.01 CI 0.51–0.91) while age, tumor size, T -stage, metastasis, renal pelvis location, and transitional cell histology were negative factors. On MVA, the highest BED3 quartile was remained significant (HR 0.69, p = 0.02; CI 0.49–0.95) as a positive factor, while age, metastasis were negative factors. Conclusion: Higher BED may be associated with improved OS. Prospective investigation is needed to clearly define optimal BED for SBRT used to treat RCC.